Green method for quantification of gatifloxacin in eye drops using UV by eco-scale assessment - Teixeira, Max Well Silva; Gil, Eric de Souza; Kogawa, Ana Carolina (Drug Analytical Research, 2026)
Gatifloxacin (GAT), a fluoroquinolone, does not present a monograph described in official compendia and the literature presents some analytical methods for its evaluation, but with space for eco-efficient methods. The objective was to develop and validate a green and indicative of stability method by UV for quantitative evaluation of GAT in eye drops. Purified water, as a diluent, quartz cubette and 286 nm were used. The method was linear in the range of 4 – 12 µg mL-1 (0.9997), precise (RSD < 5 %), selective in the comparison of standard and sample and by the forced degradation, exact with average recovery of 100.21 %, robust against changes in wavelength, source of purified water and use of ultrasound. The method was able to quantify and evaluate the stability of GAT in eye drops in green form according to the Eco-Scale Assessment.